2011
DOI: 10.1111/j.1471-4159.2011.07474.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of neuronal cholesterol biosynthesis with lovastatin leads to impaired synaptic vesicle release even in the presence of lipoproteins or geranylgeraniol

Abstract: J. Neurochem. (2011) 119, 1002–1015. Abstract Cholesterol is highly enriched in the brain, and plays a key role in synapse formation and function. The brain does not derive cholesterol from the circulation; instead, the majority of cholesterol is made in glia and secreted in form of lipoproteins. Neurons can synthesize cholesterol, but the extent of neuronal cholesterol biosynthesis in the adult brain is unknown. Cholesterol biosynthesis inhibitors of the statin family are widely used to lower circulating chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 57 publications
1
38
0
Order By: Relevance
“…Interestingly, the extracellular N-terminus of APP contains a cholesterol-binding site (Barrett et al, 2012). Optimal brain function might also be compromised if the level of cholesterol in neurons drops below a threshold level, because when the cholesterol content of hippocampal neurons was decreased by statin treatment, synaptic density was reduced and synaptic vesicle release was impaired (Mailman et al, 2011). …”
Section: Cholesterol and Admentioning
confidence: 99%
“…Interestingly, the extracellular N-terminus of APP contains a cholesterol-binding site (Barrett et al, 2012). Optimal brain function might also be compromised if the level of cholesterol in neurons drops below a threshold level, because when the cholesterol content of hippocampal neurons was decreased by statin treatment, synaptic density was reduced and synaptic vesicle release was impaired (Mailman et al, 2011). …”
Section: Cholesterol and Admentioning
confidence: 99%
“…However, current knowledge is not sufficient to quantify the effect of CSI treatment on brain cholesterol. High doses (80 mg per day) of simvastatin did reduce the synthesis of CNS cholesterol in vivo (as analyzed by the efflux of 24(S)-hydroxycholesterol) [93] and the highly lipophilic lovastatin inhibited cholesterol synthesis and synaptogenesis in vitro [122]. The analysis of the ratio of plasma 24(S)-hydroxycholesterol to cholesterol after treatment of patients with high doses of CSI, however, revealed a decreased ratio and it was postulated that this was caused by a diminished substrate supply for CYP46A1 in the brain [93].…”
Section: Cholesterol Synthesis Inhibitorsmentioning
confidence: 99%
“…Even if every cell type is able to synthesize it, it has been demonstrated that astrocytes produce from two- to three-fold more cholesterol than neurons [31] and deliver it to neuronal cells via apolipoproteins (ApoE, ApoD, ApoJ, ApoA1) [32]. The brain is the most cholesterol-rich region of the mammalian body, and this molecule is crucial to neurons, as it influences the synaptic function due its structural role in the synaptic membrane [33]. For this reason a perturbation of this metabolic pathway often leads to a pathological condition.…”
Section: Generalities On Mevalonate Pathway In the Central Nervous Symentioning
confidence: 99%